(untitled) (Computer systems and information technologies, 2024)
The overarching task to create the intelligent environment for human existence becomes the hot area of application of recent developments in information technology. The large number of articles dedicated to ambient intelligence creates the need for analysis and reflection on different aspects of this. The article aims to provide comparison and insights into the evolution of architectural solutions for intelligent homes. It starts with the definition of main terms, provides the requirements for smart home systems. The analysis of recent surveys in intelligent homes allowed to build the concept map of the area. Next, different architectural solutions proposed in literature are discussed using multi-layer model. The recent developments in the security and access rights management for intelligent homes were also analyzed. The article explores the evolution of architectural solutions for intelligent homes that ensure comfort, security, and energy efficiency in residential spaces. By analyzing historical trends, modern innovations, and promising technologies, key stages of development in architectural solutions for smart homes are identified. The focus is on integrating Internet of Things (IoT) technologies, automation systems, energy-efficient technologies, and their impact on architectural planning and residential design. The article covers aspects such as the adaptability of architectural solutions to technological changes, the integration of smart systems into building structures, the provision of convenient management and monitoring of home systems, and the enhancement of energy efficiency and environmental sustainability of residential buildings. Issues of security and privacy in the context of smart technologies are also addressed. Research methods include literature analysis, comparison of existing architectural approaches and technological solutions, and expert evaluation. The results of the study demonstrate how architectural solutions have evolved from traditional approaches to modern integrated systems that ensure high levels of comfort, security, and efficient resource use. The scientific novelty of the study lies in the comprehensive analysis of the evolution of architectural solutions for intelligent homes, focusing on technological innovations and their impact on the residential environment. The article offers practical recommendations for architects, designers, and developers of smart systems, contributing to the creation of comfortable, secure, and environmentally sustainable living spaces.